Суще та належне у фінансовому праві: основні типии доктринальних вирішень - Пацурківський, П.С. (Інститут держави і права ім. В.М. Корецького НАН України, 2003)
В статье с позиций принципа социального натурализма анализируются основные типы доктринальных подходов к определению сущего и должного в финансовом праве. Одно из центральных мест в исследовании отведено бывшему социалистическому типу понимания финансового права -юридическому позитивизму в финансовом праве, который и в настоящее время продолжает определять сущее финансовое право Украины. В статье наибольшее внимание уделено анализу данной отросли с позиций социологического позитивизма, позволяющего наиболее полно увидеть в финансовом праве должное его содержание с целью превращения его в последующем в новое сущее право постсоциалистических государств. Taking the standpoint of the principle of social naturalism, the article presents an analysis of main types
of doctrinal approaches to the definition of intrinsic and proper in financial law. The so-called “socialist”
type of understanding of financial law, nowadays considered to be that of the past, that still continues to determine
the present financial law of Ukraine, receives a preferred, in terms of allotted attention, treatment in
the analysis. The article dedicates considerable attention to the analysis of the said branch of the law based
on the position of sociological positivism, which most profoundly allows to see the intrinsic in the financial law with the purposes of reforming it into a new intrinsic law of the post-soviet states.